Ossification: a new approach to immobilize metal complex catalysts - applications to carbonylation and Suzuki coupling reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Journal of Catalysis, 2006)
A simple approach for immobilization of transition metal complexes is reported here based on the transformation of the complex into its intrinsically insoluble counterpart, thus generating solid molecular catalysts. This approach that we call ``ossification'' is based on a principle, in which the water-soluble analogues of the metal complexes are precipitated out from aqueous solutions as insoluble ionic ensembles having catalytically active metal-centered coordination environments and robust framework. The approach has been illustrated for I'd complex catalyzed carbonylation and Suzuki coupling reactions. ``Ossification'' was found to be an economically and environmentally attractive alternative to other exotic immobilization methodologies. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Carbonylation; Heterogeneous catalysts; Immobilization; ossification; Palladium complex; Suzuki coupling

Oxidative carbonylation of amine using water-soluble palladium catalysts in biphasic media - Didgikar, Mahesh R.; Joshi, Sunil S.; Gupte, Sunil P.; Diwakar, Makarand M.; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2011)
Application of water-soluble palladium catalysts for oxidative carbonylation of aniline to N,N' diphenyl urea (DPU) has been reported. The water-soluble palladium catalysts prepared from sulfonated N-containing ligands were found to be highly stable under reaction conditions and easily recyclable due to insoluble urea product in the reaction medium. This is in contrast to the sulfonated phosphine ligands, which are vulnerable to oxidation under reaction conditions, showing poor activity and stability. Commercially available as well as laboratory synthesized ligands were used for preparing water-soluble palladium catalysts, for oxidative carbonylation of aniline. The best activity was obtained for Pd complex with disodium 2,2'-bipyridine-4,4'-disulfonate (Bipy-DS) ligand. Under optimized conditions Pd(BipyDS)Pd(OAc)(2) catalyst gave TOF of similar to 210h(-1) with aniline conversion of similar to 97% with similar to 91% selectivity for N.N'-diphenyl urea. It was found that the catalyst was easily reusable up to five times, with negligible loss in the catalytic activity. The effect of reaction parameters was investigated and a plausible reaction mechanism has been proposed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amine; Biphasic catalysis; Carbonylation; Urea; Water-soluble palladium catalyst